2021
DOI: 10.1097/tp.0000000000003576
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation of Risk Factors for Pneumocystis jirovecii Pneumonia in Adult Solid Organ Transplant Recipients: A Systematic Review and Meta-analysis

Abstract: Background. There is no consensus guidance on when to reinitiate Pneumocystis jirovecii pneumonia (PJP) prophylaxis in solid organ transplant (SOT) recipients at increased risk. The 2019 American Society of Transplantation Infectious Diseases Community of Practice (AST IDCOP) guidelines suggested to continue or reinstitute PJP prophylaxis in those receiving intensified immunosuppression for graft rejection, cytomegalovirus (CMV) infection, higher dose of corticosteroids, or prolonged neutropenia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 73 publications
1
34
1
Order By: Relevance
“…IA is associated with high rates of graft loss and mortality, with a 12-month survival of 59% [ 13 , 14 ]. CMV infection has been a well-described risk factor for post-transplant Pneumocystis jirovecii pneumonia (PJP), formerly known as Pneumocystis carinii pneumonia (PCP) [ 15 , 16 , 17 ]. However, there are conflicting data with respect to the impact of post-transplant CMV on subsequent IA occurrence in SOT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…IA is associated with high rates of graft loss and mortality, with a 12-month survival of 59% [ 13 , 14 ]. CMV infection has been a well-described risk factor for post-transplant Pneumocystis jirovecii pneumonia (PJP), formerly known as Pneumocystis carinii pneumonia (PCP) [ 15 , 16 , 17 ]. However, there are conflicting data with respect to the impact of post-transplant CMV on subsequent IA occurrence in SOT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…A case was described in a newly diagnosed HIV patient with COVID-19 who presented a severe depletion of CD4 T cells, fine reticular changes in CT scan, and an elevated level of lactate dehydrogenase (LDH), successfully treated with TMP-SMX [3]. Another case involved a renal transplant recipient with lymphocytopenia treated with tacrolimus, mycophenolate mofetil, and methylprednisolone [4,9]. He died despite a treatment by TMP-SMX.…”
Section: Discussionmentioning
confidence: 99%
“…Taking GCs is a risk factor for fungal infections, including mucormycosis[ 71 ] and invasive Aspergyllosis [ 72 , 73 ]. Although the American Society of Transplantation suggests re-initiation of Pneumocystis jirovecii pneumonia (PJP) prophylaxis with intensification of immunosuppression, such as treatment of acute rejection with GCs[ 74 ], the association between GC bolus for acute rejection and PJP remains controversial[ 75 ]. While a French case-control study exhibited GC bolus administration for acute rejection in kidney transplant patients as an independent factor correlated with PJP[ 76 ] and a Korean study showed that taking GCs is significantly associated with PJP[ 77 ], a meta-analysis found that GC injections for acute rejection did not increase the risk of PJP[ 75 ].…”
Section: Side Effectsmentioning
confidence: 99%